Registration of 'Hilliard' wheat. Issue 3 (22nd September 2020) - Griffey, Carl; Malla, Subas; Brooks, Wynse; Seago, John; Christopher, Anthony; Thomason, Wade; Pitman, Robert; Markham, Robin; Vaughn, Mark; Dunaway, David; Beahm, Mary; Barrack, C. Lin; et al.
Abstract: 'Hilliard' (Reg. no. CV‐1163, PI 676271), a soft red winter (SRW) wheat ( Triticum aestivum L.) developed and tested as VA11W‐108 by the Virginia Agricultural Experiment Station, was released in March 2015. Hilliard was derived from the cross '25R47'/'Jamestown'. Hilliard is widely adapted, from Texas to Ontario, Canada, and provides producers with a mid‐season, medium height, awned, semi‐dwarf ( Rht 2) cultivar that has very high yield potential, good straw strength, and intermediate grain volume weight and quality. It expresses moderate to high levels of resistance to most diseases prevalent in the eastern United States and Ontario. In the 2016–2018 USDA‐ARS Uniform SRW Wheat nurseries, Hilliard ranked first in grain yield in the southern nursery across all 3 yr (5, 147–5, 758 kg ha −1 ). In the uniform eastern nursery, it ranked first for grain yield in 2016 (6, 159 kg ha −1 ) and 2017 (5, 633 kg ha −1 ) and second in 2018 (5, 515 kg ha −1 ). Grain volume weights of Hilliard were similar to overall trial averages in the uniform southern (73.4–75.2 kg hl −1 ) and eastern (70–75.8 kg hl −1 ) nurseries. Hilliard has soft grain texture with flour softness equivalent values varying from 58.1 to 61.7 g 100 g −1 . Straight grade flour yields on a Quadrumat Senior mill varied from 66.8 to 68.4 g kg −1 . Flour protein concentration varied from 7.0 to 9.1 g 100 g −1 and gluten strength from 108 to 128 g 100 g −1, as measured by lactic acid solvent retention capacity. Cookie spread diameter varied from 18.3 to 18.6 cm.